2016
DOI: 10.1038/ncomms11050
|View full text |Cite
|
Sign up to set email alerts
|

Controllable positive exchange bias via redox-driven oxygen migration

Abstract: Ionic transport in metal/oxide heterostructures offers a highly effective means to tailor material properties via modification of the interfacial characteristics. However, direct observation of ionic motion under buried interfaces and demonstration of its correlation with physical properties has been challenging. Using the strong oxygen affinity of gadolinium, we design a model system of GdxFe1−x/NiCoO bilayer films, where the oxygen migration is observed and manifested in a controlled positive exchange bias o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 46 publications
2
98
0
Order By: Relevance
“…These results indicate that the ferromagnetic Fe and van der Waals stacking of antiferromagnetic CoOEP layers are antiferromagnetically coupled at their interface . Note that antiferromagnetic coupled inorganic heterostructures have also shown disentangled ferromagnetic interfaces . Figure c,d represent schematic spin configurations of the Fe/CoOEP system for low H FC and high H FC cases, respectively.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These results indicate that the ferromagnetic Fe and van der Waals stacking of antiferromagnetic CoOEP layers are antiferromagnetically coupled at their interface . Note that antiferromagnetic coupled inorganic heterostructures have also shown disentangled ferromagnetic interfaces . Figure c,d represent schematic spin configurations of the Fe/CoOEP system for low H FC and high H FC cases, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…In this wise, ferromagnetic Fe film could be the best candidate to accommodate the antiferromagnetic interfacial interaction as its surface could be partially oxidized. This unusual antiferromagnetic interface coupling at a ferromagnet/antiferromagnet bilayer has been extensively studied in an inorganic system exhibiting inversion of exchange bias with controllable anisotropy, but not realized in an organic system yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that the perpendicular exchange coupling across the ferromagnetic/antiferromagnetic interface can influence both the coercivity and the PMA of a ferromagnetic sublayer in permalloy/CoO,22 CoPt/CoO,23 Co/CoO,24,25 and Fe/Mn26 systems. This provides a powerful platform for tailoring PMA as well as realizing emergent voltage‐controlled functionalities 27,28. In this work, interfacial exchange coupling of magnetic moments between ferromagnetic metal and antiferromagnetic oxides is used as an extra source to stabilize the perpendicular magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of the FM layer magnetization sets the orientation of the interfacial AFM spins because of the interface exchange coupling between the two layers. Other ways of controlling and manipulating exchange bias have been very recently * Corresponding author: Stephane.mangin@univ-lorraine.fr investigated relying on ionic motion at interfaces [18] or modifying the crystal structure [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental mechanism explaining exchange bias has been discussed extensively [19][20][21][22] but remains a topic of high interest [23,18]. Ultrafast optical excitations of an AFM/FM bilayer have been used to probe the interfacial interaction between the AFM and the FM layers, and interesting fast magnetization dynamics have already been observed [24][25][26].…”
Section: Introductionmentioning
confidence: 99%